KAJIAN EFISIENSI PANAS KOLEKTOR PEMANAS AIR SURYA PADA MOBILE MINI BIODIESEL PLANT - Rinjani Rakasiwi; Syaifurrahman Syaifurrahman; Wivina Diah I; Usman A Gani (Jurnal Rekayasa Mesin, 2022)
Integration of solar water heating system and biodiesel unit process has resulted a prototype called Mini Biodiesel Plant. The key of that unit is the effectiveness of heat transfer that occured in the solar collector. The purpose of this research is to analyze the performance of the collector from the solar water heating system. The solar collector used is a flat plate type with a surface area of 0.7m2. It consists of a glass cover, alummunium absorber, styrofoam insulator and woof frame. Based on the research result for 5 times for 5 hours each day, the highest of intensity of solar radiation (I) was 859 W/m2 can produce  maximum hot water (Ta) of 62oC. The average of real heat has been absorbes by teh collector (Qu) was 271 Watt while the maximum of heat loss (Qloss) was 144.6 Watt therefore the average of collector efficiency (ƞ) was 45.1%.